Necropsy techniques for examining wildlife samples - Garcês, Andreia; Pires, Isabel (Bentham Books, 2020)
In this handbook, the authors provide a practical, easily accessible guide of necropsy techniques for examining wildlife. Chapters introduce the reader to the value of necropsy in studying wildlife in general, sample collection methods, cadaveric phenomena and necropsy techniques for a variety of organisms ranging from invertebrates to mammals. The book addresses some of the peculiar characteristics of veterinary autopsy specific to different types of specimens. The goal of this book is to equip the reader with the information necessary to conduct a forensic examination in order to reach a con.